2001
DOI: 10.1055/s-0038-1634429
|View full text |Cite
|
Sign up to set email alerts
|

Automated Nasopharyngeal Carcinoma Detection with Dynamic Gadolinium-Enhanced MR Imaging

Abstract: Summary Objectives: The purpose of this research is to develop an automatic medical diagnosis for segmenting nasopharyngeal carcinoma (NPC) with dynamic gadolinium-enhanced MR imaging. Methods: This system is a multistage process, involving motion correction, head mask generation, dynamic MR data quantitative evaluation, rough segmentation, and rough segmentation refinement. Two approaches, a relative signal increase method and a slope method,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Studies reported on computer segmentation of NPC are scarce, which may be partly due to the low incidence of NPC in most countries. Hsu et al developed an automatic medical diagnosis for segmenting NPC with dynamic MRI and pharmacokinetic analysis [4]. This method can identify the NPC regions effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported on computer segmentation of NPC are scarce, which may be partly due to the low incidence of NPC in most countries. Hsu et al developed an automatic medical diagnosis for segmenting NPC with dynamic MRI and pharmacokinetic analysis [4]. This method can identify the NPC regions effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al (1999) applied a relative signal increase curve to identify recurrent tumors. Hsu et al (2001) used pharmacokinetic analysis to identify the NPC region. Zhou et al (2003) presented a fuzzy clustering method to filter out normal tissue regions in T1-weighted (T1W) and contrast-enhanced T1W images.…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported on computer-aided segmentation of NPC from MRI slices are scarce. Among several existing studies, Hsu et al [7] developed an automatic medical diagnosis approach for segmenting NPC with dynamic MRI and pharmacogenetic analysis. This method is only capable of identifying NPC, which makes it a type of "detection" rather than "segmentation" method.…”
Section: Introductionmentioning
confidence: 99%